Catalytic Hydrogen Production by Ruthenium Complexes from the Conversion of Primary Amines to Nitriles: Potential Application as a Liquid Organic Hydrogen Carrier. Issue 49 (10th November 2016) - Ventura‐Espinosa, David; Marzá‐Beltrán, Aida; Mata, Jose A.
Abstract: The potential application of the primary amine/nitrile pair as a liquid organic hydrogen carrier (LOHC) has been evaluated. Ruthenium complexes of formula [( p ‐cym)Ru(NHC)Cl2 ] (NHC=N‐heterocyclic carbene) catalyze the acceptorless dehydrogenation of primary amines to nitriles with the formation of molecular hydrogen. Notably, the reaction proceeds without any external additive, under air, and under mild reaction conditions. The catalytic properties of a ruthenium complex supported on the surface of graphene have been explored for reutilization purposes. The ruthenium‐supported catalyst is active for at least 10 runs without any apparent loss of activity. The results obtained in terms of catalytic activity, stability, and recyclability are encouraging for the potential application of the amine/nitrile pair as a LOHC. The main challenge in the dehydrogenation of benzylamines is the selectivity control, such as avoiding the formation of imine byproducts due to transamination reactions. Herein, selectivity has been achieved by using long‐chain primary amines such as dodecylamine. Mechanistic studies have been performed to rationalize the key factors involved in the activity and selectivity of the catalysts in the dehydrogenation of amines. The experimental results suggest that the catalyst resting state contains a coordinated amine. Abstract : A system of support : The potential application of the primary amine/nitrile pair as a liquid organic hydrogen carrier (LOHC) has been evaluated. Molecular ruthenium complexes, [( p ‐cym)Ru(NHC)Cl2 ] (NHC=N‐heterocyclic carbene; see scheme), are active in the dehydrogenation of primary amines to nitriles with the simultaneous formation of two moles of molecular hydrogen. The reaction proceeds without any external additive under mild conditions.